Asas Legalitas dalam Kepastian Hukum Terhadap Praktek Kartel Usaha Breeding Farm (Studi Putusan KPPU Nomor 02/KPPU-I/2002) - zaini Munawir (Universitas Medan Area, 2020)
This paper analyzes the decision of KPPU Number 02 / KPPU-I / 2002 concerning the principle of legality in legal certainty towards the practice of Breeding Farm Business Cartel, where the business man carries out a cartel in the form of GPPU or Poultry Farmers Association and has entered into an agreement regarding price and stock, but its nature incidental and occurred before the enactment of Law Number 5 of 1999 and not continued after the enactment of Law Number 5 of 1999 which is March 5, 2000. The method in this research is normative juridical research (normative legal research methods). Normative juridical research methods are library legal research conducted by examining library materials or secondary data. The results found are that although the agreement elements in Article 11 of Law Number 5 Year 1999 have been fulfilled according to the KPPU, the agreement is incidental in nature which only occurs when the breeders provide price relief to the breeder's cooperative at the end of 1999 and currently the agreement is no longer valid, so as such the element of agreement in Article 11 of Law Number 5 of 1999 is not fulfilled and it can be said that the cartel conducted prior to the entry into force of Law Number 5 of 1999